PENGARUH KUALITAS KEHIDUPAN KERJA DAN KOMUNIKASI DENGAN KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA PEGAWAI (STUDI PADA LPMP PROVINSI JAWA TENGAH) - Noviana, Ulfa; Rijanti, Tristiana (Jurnal Ilmiah Telaah Manajemen, 2014)
Performance of employees in LPMP Central Java has not been optimally marked by the presence of mentoring activities that should be done in each district / city in Central Java region in order to provide assistance to units and educational programs in the form of quality assurance activities in units and educational programs that have not met target. This study aims to examine and analyze the effect of quality of work life and communication on performance with job satisfaction and organizational commitment as intervening variable. Technique sample using purposive sampling technique, with criterion of civil servant and working period more than 3 years, education minimum D3 counted 123 people. Instrument test is done by using factor analysis that is with the validity test and reliablilitas test. Data analysis using multiple linear regression to test the hypothesis. The results showed that quality of work life have positively significantly effect to job satisfaction, communication have positively significantly effect to job satisfaction, communication have positively significantly to organizational commitment, quality of work life have positively significantly to organizational commitment,job satisfaction has no effect to organizational commitment, quality of work life has no effect to performance, communication have positively significantly effect to performance, job satisfaction have negatively effect to performance, organizational commitment have positively significantly effect on performance, job satisfaction as mediating variable the effect of quality of work life to performance,job satisfaction as mediating variable the effect ofcommunication to performance, commitment organizationalas mediating variable the effect of quality of work life to performance, commitment organizationalis not a mediating variable the effect ofcommunication to performance, job satisfaction and commitment organizational is a mediating variable influence both quality of work life on performance and communication to performance. The most dominant variable affecting job satisfaction is communication, the most dominant variable influencing organizational commitment is communication whereas the most influential variable affecting performance is organizational commitment Keywords: Quality of Work Life, Communication, Job Satisfaction, Organizational Commitment, Performance